Can the RUVIS Reflected UV Imaging System Visualize Fingerprint Corrosion on Brass Cartridge Casings Postfiring?. Issue 3 (12th March 2013) - Leintz, Rachel; Bond, John W.
Abstract Comparisons are made between the visualization of fingerprint corrosion ridge detail on fired brass cartridge casings, where fingerprint sweat was deposited prefiring, using both ultraviolet (UV) and visible (natural daylight) light sources. A reflected ultraviolet imaging system (RUVIS), normally used for visualizing latent fingerprint sweat deposits, is compared with optical interference and digital color mapping of visible light, the latter using apparatus constructed to easily enable selection of the optimum viewing angle. Results show that reflected UV, with a monochromatic UV source of 254 nm, was unable to visualize fingerprint ridge detail on any of 12 casings analyzed, whereas optical interference and digital color mapping using natural daylight yielded ridge detail on three casings. Reasons for the lack of success with RUVIS are discussed in terms of the variation in thickness of the thin film of metal oxide corrosion and absorption wavelengths for the corrosion products of brass.